Effects of Direct Thermal Method Processing Parameters on Mechanical Properties of Semisolid A6061 Feedstock - M. Tajudin, M. F.; Ahmad, A. H.; Rashidi, M. M. (International Journal of Automotive and Mechanical Engineering, 2021)
This paper highlights the effects of pouring temperature and holding time on the mechanical properties of aluminium 6061 semisolid feedstock billets. The semisolid metal feedstock billets were prepared by a direct thermal method (DTM), in which the molten metal was poured into a cylindrical copper mould with a different combination of pouring temperature and holding time before it was solidified in room temperature water. The results show that the sample with pouring temperature slightly above aluminium 6061 liquidus temperature has the lowest porosity, thereby the highest mechanical properties value. The sample with a pouring temperature of 660 °C and holding time of 60 s has the density, tensile strength and hardness properties of 2.701 g/cm3, 146.797 MPa, and 86.5 HV, respectively. Meanwhile, the sample at a pouring temperature of 640 °C and holding time of 20 s has density, tensile strength and hardness properties of 2.527 g/cm3, 65.39 MPa, and 71.79 HV, respectively. The density and fractography tests were conducted to confirm the existence of porosity within the samples. The results from these experimental works suggested that the mechanical properties of DTM semisolid feedstock billet merely depended on processing parameters, which influenced the porosity level within the feedstock billet, thus directly affected their mechanical properties.